Method for rapidly screening fireproof materials
Through image analysis technology, the volume change pattern of fireproof materials at high temperatures is clarified, and the existing fireproof materials are solved, which is the problem of high-weight and low cost-effectiveness, and the fireproof performance and cost-effectiveness of high-rise/super-high-rise buildings are improved.
Patent Information
- Application Number
- CN202411023994.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2024-12-20
AI Technical Summary
The existing fireproof materials are large per unit area in high-rise/super-high-rise buildings, and the overall cost-effectiveness is not high, making it difficult to fully adapt to the fire protection needs of high-rise/super-high-rise buildings. The volume changes of inorganic binders and reinforcing fibers at high temperatures are not ruled. It has been fully studied and affects fire resistance.
By taking images of fireproof materials at different temperatures, using image analysis software to calculate pixels, draw temperature-pixel maps, clarify the volume change rules of inorganic binders and reinforcement fibers, and quickly screen out suitable fireproof materials.
It improves the screening efficiency and performance of fireproof materials, provides fire resistance limits and thermal insulation performance suitable for high-rise/super-high-rise buildings, optimizes the structure of fireproof coatings, and improves the comprehensive cost-effectiveness.
Smart Images

Figure CN119168940A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fireproof materials, and in particular to a method for quickly screening fireproof materials. Background Art
[0002] In recent years, fire accidents in high-rise / super-high-rise buildings have occurred frequently, and high-rise / building fires have a fast vertical spread speed, a large number of combustibles, difficulty in external rescue, high risks of smoke and toxic gases, and a lack of major rescue means. High-rise / super-high-rise buildings still rely mainly on self-rescue. Therefore, improving the fire protection level and protection effect of buildings has been mentioned as the primary consideration. According to the fire protection characteristics of high-rise / super-high-rise buildings, facing the requirements of high fire resistance limit, good weather resistance, good flexibility, high strength, easy construction, and low surface density of fire protection materials, it is urgent to develop fireproof materials that meet the characteristics of high-rise / super-high-rise buildings. Existing fireproof materials have the problems of large unit area weight and low comprehensive cost performance, which makes it difficult to fully adapt to the characteristics of high-rise / super-high-rise buildings. Therefore, it is urgent to optimize the structure of protective materials to adapt to the multi-layer fire protection technology of different temperature sections and different fireproof materials, so as to improve the comprehensive cost performance of fire protection products and adapt them to the characteristics of high-rise / super-high-rise fire protection, so as to provide long-term fire protection for high-rise / super-high-rise buildings.
[0003] Among the existing high-rise fire protection products, fireproof panels and fireproof coatings are the most mature, and both can meet the fire resistance limit requirements of 3.00h-4.00h for high-rise / super-high-rise walls or load-bearing structures. According to national standard classification, my country's steel structure fire retardant coatings are mainly divided into intumescent steel structure fire retardant coatings and non-intumescent steel structure fire retardant coatings. At present, in the domestic high-rise and super-high-rise steel structure (or fire resistance limit exceeds 2.50h) building fire protection design, it is recommended to use non-intumescent steel structure fire retardant coatings, which are mainly used for fire protection of load-bearing components.
[0004] Inorganic binder is one of the main components of non-expanding fire retardant coating for steel structure. The binder not only combines the heat insulation material, flame retardant material, refractory material, refractory fiber and additives of the fire retardant coating, but also tightly binds the fire retardant coating to the surface of the steel structure to ensure that the volume of the fire retardant coating remains relatively stable at high temperature and maintain the heat insulation performance of the fire retardant coating. The current research mainly focuses on the thermal performance of refractory binders, without considering the heat insulation performance, and has not studied the failure law of inorganic binders of fire retardant coatings.
[0005] Reinforcement fiber is a kind of reinforced insulation material used in non-expanding steel structure fire retardant coatings. It not only has the advantages of general fiber such as softness, high strength, high ductility, good crack resistance, but also has high temperature resistance, heat insulation and oxidation resistance. The functions of refractory reinforcement fiber mainly include heat insulation, reinforcement, filling and support, which can improve the thermal insulation, fire resistance and high temperature stability of fire retardant coatings. There are many kinds of reinforcement fibers, including inorganic refractory fibers and organic refractory fibers. Although the decomposition of organic refractory fibers at high temperatures causes the ductility of refractory materials to decrease and crack, which affects the fire resistance of materials in high temperature environments and the mechanical properties of fireproof materials, it is beneficial to improve the mechanical properties of cement-based fireproof materials at room temperature. The current research mainly focuses on the decomposition of fibers, and has not tested the volume change law of fibers at high temperatures. Summary of the invention
[0006] The purpose of the present invention is to provide a method for quickly screening fireproof materials, by measuring the volume change law of inorganic binders and reinforcing fibers to achieve rapid screening of the two, and further improve the screening efficiency and fireproof performance of fireproof materials.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] A method for rapidly screening fireproof materials comprises the following steps: taking images of various fireproof materials at different temperatures, using image analysis software to calculate pixels at different temperatures, and then drawing a temperature-pixel graph, and rapidly screening suitable fireproof materials according to the volume change law of various fireproof materials under high temperature conditions shown on the graph.
[0009] Furthermore, the fireproof material includes an adhesive bond and / or reinforcing fibers.
[0010] Furthermore, capturing images of each fireproof material at different temperatures includes the following steps: placing the fireproof material sample in the center of the heating furnace tray of the imaging sintering point tester, setting the heating temperature range to 20-1200°C, the heating speed to 5-20°C / min, the image capturing frequency to capture one image for every 5-20°C rise in temperature, the image capturing temperature range to 400-1200°C, and when the heating temperature reaches the set maximum value, saving the test data and ending the heating program.
[0011] Furthermore, calculating pixels at different temperatures includes the following steps:
[0012] S1. Open ImageJ software.
[0013] S2. Extracting images of each temperature point;
[0014] S3. Select a polygonal border selection tool to connect the borders of the sample image;
[0015] S4. Calculate the pixels of the image through the analysis menu of the main interface;
[0016] S5. Repeat steps S2-S4 to count the image pixels at different temperatures respectively.
[0017] Furthermore, the step of drawing a temperature-pixel graph includes: drawing a temperature-pixel graph of the inorganic binder according to the temperature and pixel table of the image processing, with the temperature as the abscissa and the volume as the ordinate.
[0018] Furthermore, when the fireproof material is a binder, the method comprises the following steps: S11, selecting two binders, a white silicate binder and a black silicate binder, and making binder test blocks respectively;
[0019] S12, using an imaging sintering point instrument, taking images of each adhesive test block at different temperatures;
[0020] S13, using ImageJ image analysis software to calculate the pixels of the image;
[0021] S14, plotting a temperature-pixel graph for each adhesive with temperature as the abscissa and pixels as the ordinate;
[0022] S15. Based on the images of each adhesive test block at different temperatures and the temperature-pixel map of each adhesive, the volume change law of each adhesive at high temperature is obtained.
[0023] Furthermore, in S11, the steps of making the adhesive test block are as follows:
[0024] S111. Take a beaker, add 90-110 g of white silicate binder / black silicate binder into the beaker, add 15-20 g of distilled water into the beaker with a plastic dropper, and then stir rapidly with a glass rod for 1-3 minutes to obtain a uniform thick paste A;
[0025] S112. Transfer paste A into the small holes of a plastic porous plate, the diameter of the small holes is 10 mm, and the height is 10 mm; use a plastering knife to smooth the paste along the upper and lower surfaces of the plastic porous plate, and then use a glass rod with a diameter of 8 mm to poke out paste A and place it flat on white paper. Dry it naturally at room temperature for 24 hours to obtain a dry adhesive test block.
[0026] Furthermore, the specific operation of S12 is as follows:
[0027] S121, pulling out the heating furnace tray of the image sintering apparatus, placing the dried binder test block in the center of the heating furnace tray, and then pushing the heating furnace tray into the heating furnace of the image sintering apparatus;
[0028] S122, turn on the host of the imaging sintering point instrument, start the operating software, and set the heating speed, heating temperature range, image shooting frequency and image shooting temperature range of the imaging sintering point instrument through the main interface; preferably, the heating speed is set to 10°C / min, the heating temperature range is set to 20-1200°C, the image shooting frequency is to shoot one image every time the temperature rises by 10°C, and the image shooting temperature range is set to 400-1200°C;
[0029] S123, rotating the camera head of the imaging sintering point instrument so that the binder test block to be heated is in the center of the camera display screen, and adjusting the focal length of the camera until the binder test block to be heated can be clearly seen on the camera display screen;
[0030] S124, placing a camera protector between the camera head and the heating furnace, and making the camera lens, the camera protector and the adhesive test block to be heated in the same straight line;
[0031] S125, turning on the power of the heating furnace;
[0032] S126, heating the adhesive test block by operating the software, and capturing images of the adhesive test block within the image capturing temperature range based on the image capturing frequency to obtain images at different temperature points;
[0033] S127, when the heating temperature reaches 1200°C, save the image and end the heating;
[0034] S128. After the adhesive test block cools to room temperature, take it out of the heating furnace, and turn off the heating furnace, operating software and host power in turn.
[0035] Furthermore, the specific operation of S13 is as follows:
[0036] S131, open ImageJ image analysis software;
[0037] S132, extracting images at different temperature points;
[0038] S133, select a polygonal border selection tool to connect the border of the image at any temperature point;
[0039] S134, calculating the pixels of the image at any temperature point through the analysis menu of the main interface of the ImageJ image analysis software;
[0040] S135. Repeat S133-S134 to calculate the pixels of the image at different temperature points.
[0041] Furthermore, when the fireproof material is reinforced fiber, the method comprises the following steps:
[0042] S21, select four types of fibers, namely basalt fiber, mineral wool fiber, carbon fiber and zirconium-containing aluminum silicate fiber as reinforcing materials;
[0043] S22, respectively preparing carbon fiber test blocks of each fiber;
[0044] S23, using an imaging sintering point instrument, taking images of each carbon fiber test block at different temperatures;
[0045] S24, using ImageJ image analysis software to calculate the pixels of the image;
[0046] S25, using temperature as the abscissa and pixel as the ordinate, drawing a temperature-pixel graph of each carbon fiber;
[0047] S26. Based on the images of each carbon fiber test block at different temperatures and the temperature-pixel map of each carbon fiber, the volume change law of each carbon fiber at high temperature is obtained.
[0048] Furthermore, the specific operation of S22 is as follows:
[0049] S221, cut any fiber into short shreds with a length of 2 mm, take 2 g, add about 0.2 g of black silicate binder and an appropriate amount of water to make a paste B;
[0050] S222. Transfer paste B into the small holes of a plastic porous plate with a diameter of 10 mm and a height of 10 mm. Gently compact paste B and smooth paste B along the upper and lower surfaces of the plastic porous plate with a plastering knife. Use a glass rod with a diameter of 8 mm to poke out paste B and place it flat on white paper. Dry it naturally at room temperature for 48 hours to obtain a dry carbon fiber test block.
[0051] Furthermore, the specific operation of S23 is as follows:
[0052] S231, pulling out the heating furnace tray of the image sintering instrument, placing the dried carbon fiber test block in the center of the heating furnace tray, and then pushing the heating furnace tray into the heating furnace of the image sintering instrument;
[0053] S232, turn on the host of the imaging sintering point instrument, start the operating software, and set the heating speed, heating temperature range, image shooting frequency and image shooting temperature range of the imaging sintering point instrument through the main interface; preferably, the heating speed is set to 10°C / min, and the image shooting frequency is 1 image per 10°C temperature rise; when heating the basalt fiber, mineral wool fiber, zirconium-containing aluminum silicate fiber corresponding to the carbon fiber test block, the heating temperature range is set to 20-1200°C, and the image shooting temperature range is set to 400-1200°C; when heating the carbon fiber corresponding to the carbon fiber test block, the heating temperature range is set to 20-700°C, and the image shooting temperature range is set to 400-700°C;
[0054] S233, rotating the camera head of the imaging sintering point instrument so that the binder test block to be heated is in the center of the camera display screen, and adjusting the focal length of the camera until the carbon fiber test block to be heated can be clearly seen on the camera display screen;
[0055] S234, placing a camera protector between the camera head and the heating furnace, and making the camera lens, the camera protector and the carbon fiber test block to be heated in the same straight line;
[0056] S235, turning on the power of the heating furnace;
[0057] S236, heating the carbon fiber test block by operating the software, and capturing images of the binder test block within the image capturing temperature range based on the image capturing frequency to obtain images at different temperature points;
[0058] S237, when the heating temperature reaches 700° C. or 1200° C., save the image and end the heating;
[0059] S238. After the carbon fiber test block cools to room temperature, take it out of the heating furnace, and turn off the heating furnace, operating software and host power in turn.
[0060] Furthermore, the specific operation of S24 is as follows:
[0061] S241, open ImageJ image analysis software;
[0062] S3242, extracting images at different temperature points;
[0063] S243, select a polygonal border selection tool to connect the border of the image at any temperature point;
[0064] S244, calculating the pixels of the image at any temperature point through the analysis menu of the main interface of the ImageJ image analysis software;
[0065] S245, repeat S243-S244 to calculate the pixels of the image at different temperature points.
[0066] Compared with the prior art, the present invention has the following beneficial effects:
[0067] 1. The present invention takes images of the binder at different temperatures, uses image analysis software to calculate the pixels at different temperatures, and then draws a temperature-pixel graph. The volume change law of the binder under high temperature conditions can be clearly seen from the temperature-pixel graph, and the best binder for the fire retardant coating can be quickly screened out.
[0068] 2. The present invention takes images of fibers at different temperatures, uses image analysis software to calculate pixels at different temperatures, and then draws a temperature-pixel graph. The temperature-pixel graph can clearly show the volume change pattern of the fibers under high temperature conditions, and then quickly screen out the best fibers for fire retardant coatings, that is, the best reinforcement material. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] Figure 1 Schematic diagram of a plastic porous plate according to an embodiment of the present invention.
[0070] Figure 2 Schematic diagram of an adhesive test block according to an embodiment of the present invention.
[0071] Figure 3 This is a diagram of the interface of ImageJ image analysis software according to an embodiment of the present invention.
[0072] Figure 4 This is an image of an adhesive test block at a certain temperature in an embodiment of the present invention.
[0073] Figure 5 This is a boundary diagram of the adhesive test block according to an embodiment of the present invention.
[0074] Figure 6 This is an image pixel calculation diagram of the adhesive test block according to an embodiment of the present invention.
[0075] Figure 7 These are images of the white silicate binder of the present invention at different temperatures.
[0076] Figure 8 This is a temperature-pixel diagram of the white silicate binder according to an embodiment of the present invention.
[0077] Fig. 9 These are images of the black silicate binder of the present invention at different temperatures.
[0078] Fig.10 FIG. 4 is a temperature-pixel diagram of the black silicate adhesive according to an embodiment of the present invention.
[0079] Fig.11 This is an image of the basalt fiber according to an embodiment of the present invention at 400°C.
[0080] Fig.12 This is an image of the basalt fiber according to an embodiment of the present invention at 1200°C.
[0081] Fig.13 These are images of basalt fibers according to an embodiment of the present invention at different temperatures.
[0082] Fig.14 This is a temperature-pixel diagram of the basalt fiber according to an embodiment of the present invention.
[0083] Fig.15 This is an image of the mineral wool fiber according to an embodiment of the present invention at 400°C.
[0084] Fig.16 This is an image of the mineral wool fiber according to an embodiment of the present invention at 1200°C.
[0085] Fig.17 These are images of mineral wool fibers at different temperatures according to an embodiment of the present invention.
[0086] Fig.18 This is a temperature-pixel diagram of the mineral wool fiber according to an embodiment of the present invention.
[0087] Fig.19 This is an image of the carbon fiber according to an embodiment of the present invention at 400°C.
[0088] Fig. 20 This is an image of the carbon fiber according to an embodiment of the present invention at 700°C.
[0089] Fig.21 These are images of carbon fibers according to an embodiment of the present invention at different temperatures.
[0090] Fig. 22 This is a temperature-pixel diagram of the carbon fiber according to an embodiment of the present invention.
[0091] Fig.23 This is an image of the zirconium-containing aluminum silicate fiber at 400°C according to an embodiment of the present invention.
[0092] Fig.24 This is an image of the zirconium-containing aluminum silicate fiber at 1200°C according to an embodiment of the present invention.
[0093] Fig.25 These are images of the zirconium-containing aluminum silicate fiber at different temperatures according to an embodiment of the present invention.
[0094] Fig.26 This is a temperature-pixel diagram of the zirconium-aluminum silicate fiber according to an embodiment of the present invention. DETAILED DESCRIPTION
[0095] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0096] Example 1
[0097] This embodiment discloses a method for rapid screening of fireproof materials of the present invention, which is as follows:
[0098] 1. Choose two types of adhesives: white silicate adhesive and black silicate adhesive;
[0099] 1.1. Make adhesive test blocks;
[0100] Take a beaker, add 100g of white silicate binder to the beaker, add 18g of distilled water to the beaker with a plastic dropper, and then stir quickly with a glass rod for 2 minutes to obtain a uniform and thick paste A; transfer the paste A into the small holes of the plastic porous plate. Figure 1 As shown, the diameter of the small hole is 10mm and the height is 10mm; use a plastering knife to smooth the paste along the upper and lower surfaces of the plastic porous plate, and then use a glass rod with a diameter of 8mm to poke out the paste A and place it flat on white paper. Dry it naturally at room temperature for 24h to obtain a dry white silicate adhesive test block, as shown Figure 2 shown.
[0101] The same method was used to prepare black silicate binder test blocks.
[0102] 1.2 Testing
[0103] Take a dried white silicate binder test block / black silicate binder test block and use an imaging sintering point tester to take an image under high temperature conditions. The steps are as follows:
[0104] 1.2.1 Pull out the heating furnace tray of the image sintering instrument, place the dry white silicate binder test block / black silicate binder test block in the center of the heating furnace tray, and then push the heating furnace tray into the heating furnace of the image sintering instrument;
[0105] 1.2.2 Turn on the host of the imaging sintering point instrument, start the operating software, and set the heating speed, heating temperature range, image shooting frequency and image shooting temperature range of the imaging sintering point instrument through the main interface; preferably, the heating speed is set to 10℃ / min, the heating temperature range is set to 20-1200℃, the image shooting frequency is to shoot 1 image for every 10℃ increase in temperature, and the image shooting temperature range is set to 400-1200℃;
[0106] 1.2.3 Rotate the camera of the imaging sintering point instrument so that the white silicate binder test block / black silicate binder test block to be heated is in the center of the camera display screen, and adjust the focus of the camera until the white silicate binder test block / black silicate binder test block to be heated can be clearly seen on the camera display screen;
[0107] 1.2.4 Place a camera protector between the camera head and the heating furnace, and make the camera lens, camera protector and the white silicate binder test block / black silicate binder test block to be heated in the same straight line;
[0108] 1.2.5 Turn on the power of the heating furnace;
[0109] 1.2.6 Heat the white silicate adhesive test block / black silicate adhesive test block by operating the software, and take images of the adhesive test block within the image taking temperature range based on the image taking frequency to obtain images at different temperature points;
[0110] 1.2.7 When the heating temperature reaches 1200°C, save the image and end the heating;
[0111] 1.2.8 After the white silicate binder test block / black silicate binder test block cools to room temperature, take it out of the heating furnace and turn off the heating furnace, operating software and host power in turn.
[0112] 1.3 Image Processing
[0113] 1.3.1. Open ImageJ image analysis software, such as Figure 3 As shown;
[0114] 1.3.2. Extract images at different temperature points, such as Figure 4 As shown;
[0115] 1.3.3. Select the polygonal selection tool and connect the borders of the image at any temperature point, such as Figure 5 As shown;
[0116] 1.3.4. Calculate the pixels of the image at any temperature point through the analysis menu of the main interface of ImageJ image analysis software;
[0117] 1.3.5. Repeat 1.3.3-1.3.4 to calculate the pixels of the image at different temperature points.
[0118] Through the above operations, pixels of the images of the white silicate binder test block / the black silicate binder test block at different temperature points are obtained.
[0119] 1.4 Pixel Processing
[0120] With temperature as the abscissa and pixels as the ordinate, a temperature-pixel graph of the white silicate binder / black silicate binder is plotted.
[0121] 1.5 Analysis
[0122] 1.5.1. Volume change of white silicate binder at high temperature
[0123] like Figure 7 As shown, images of white silicate binder in a high temperature furnace were taken every 10°C starting from 400°C.
[0124] from Figure 7It can be seen from the graph that as the temperature rises, the image volume (pixels) of the white silicate binder is shrinking. The reduction in volume is not significant when observed with the naked eye, and the temperature at which the image area is reduced cannot be seen from the graph. Therefore, it is difficult to determine the maximum temperature that the white silicate can withstand from the image alone.
[0125] like Figure 8 As shown in the figure, when the temperature of the white silicate binder increases from 400℃ to 650℃, the pixels of the white silicate binder decrease, that is, the volume gradually decreases. This is because the bound water of the hydrated white silicate binder begins to be removed at 300℃, and the reduced bound water leaves the white silicate binder, and the volume gradually decreases; when the temperature rises to 650℃, the bound water is completely removed, and its volume reaches the minimum; when the temperature of the white silicate binder increases from 650℃ to 870℃, the volume of the white silicate binder gradually increases. At this time, the white silicate binder The quartz crystal form in the binder changes. When quartz changes from β quartz to α quartz, the two Si-O tetrahedrons in its crystal structure are connected and straightened to 180°, and the volume expansion rate of quartz increases dramatically; when heated to 870℃, α quartz turns into phosphotyrrolidone, and the volume expansion rate of quartz increases dramatically again; when the temperature of the white silicate binder rises from 870℃ to 1150℃, the low-melting-point oxides such as KO and NaO in the white silicate binder melt and the volatile SO3 overflows, and the volume of the white silicate binder shrinks sharply.
[0126] In summary, we can draw the law of volume change of white silicate binder at high temperature. When the temperature rises to about 900℃, the volume of white silicate binder is significantly reduced. The reduced volume increases the stress of the fire retardant coating. When the stress increases to the limit, cracks appear in the coating, resulting in failure of the coating protection.
[0127] 1.5.2. Volume change of black silicate binder at high temperature
[0128] like Fig. 9 As shown, images of the black silicate binder in a high temperature furnace were taken every 10°C starting from 400°C.
[0129] from Fig. 9 As can be seen from the graph, as the temperature increases, the image pixels of the black silicate binder increase, but the increase is not obvious, and it is difficult to determine the temperature when the image increases significantly from the graph. Therefore, it is difficult to determine the extent of the volume increase of the black silicate only from the image.
[0130] like Fig.10As shown in the figure, during the whole heating process, as the temperature increases, the pixels of the black silicate binder specimen increase, so the volume of the black silicate binder increases. When the temperature of the black silicate binder increases from 400℃ to 700℃, the volume of the black silicate binder increases slowly, which is mainly due to the fact that the thermal expansion and volume contraction of the black silicate binder reach a balance; when the temperature increases from 700℃ to 1200℃, the volume of the black silicate increases rapidly.
[0131] 1.5.3. Rapidly screen out the best binder for fire retardant coatings based on the volume change law of white silicate binder / black silicate binder at high temperature
[0132] By taking images of silicate binder at different temperatures, using image analysis software to calculate the pixels at different temperatures, and then drawing a temperature-pixel graph, we can clearly see the volume change law of the silicate binder of the fire retardant coating under high temperature conditions: in the heating range of 400℃-1200℃, as the temperature increases, the overall trend of the volume of the white silicate binder is to decrease, and the overall trend of the volume of the black silicate binder is to increase.
[0133] Relying solely on a single white silicate binder or a black silicate binder is not conducive to maintaining the volume stability of the fire retardant coating at high temperatures. Therefore, a compound system of white silicate and black silicate binders is used as the best binder for the fire retardant coating.
[0134] According to the temperature distribution law of the fire site, white silicate binder with low density and good thermal insulation is suitable as inorganic binder for 500℃-800℃ fireproof and thermal insulation layer; black silicate binder with high density and good heat resistance is suitable as inorganic binder for fire-resistant layer above 800℃.
[0135] 2. Select four types of fibers: basalt fiber, mineral wool fiber, carbon fiber, and zirconium-containing aluminum silicate fiber as reinforcement materials;
[0136] 2.1 Make carbon fiber test blocks;
[0137] Cut the basalt fiber into short strips with a length of 2 mm, take 2 g, add about 0.2 g of black silicate binder and an appropriate amount of water to make a paste B; gently compact the paste B, smooth the paste B along the upper and lower planes of the plastic porous plate with a plastering knife, and then poke out the paste B with a glass rod with a diameter of 8 mm, and place it flat on white paper, and dry it naturally at room temperature for 48 hours to obtain a dry basalt fiber carbon fiber test block.
[0138] The same method was used to prepare carbon fiber test pieces of mineral wool fiber, carbon fiber, and zirconium-containing aluminum silicate fiber.
[0139] 2.2 Testing
[0140] Take a dried carbon fiber test block (basalt fiber / mineral wool fiber / carbon fiber / carbon fiber test block containing zirconium-type aluminum silicate fiber) and use an imaging sintering point tester to take an image under high temperature conditions. The steps are as follows:
[0141] 2.2.1. Pull out the heating furnace tray of the image sintering instrument, place the dry carbon fiber test block in the center of the heating furnace tray, and then push the heating furnace tray into the heating furnace of the image sintering instrument;
[0142] 2.2.2. Turn on the host of the imaging sintering point instrument, start the operating software, and set the heating speed, heating temperature range, image shooting frequency and image shooting temperature range of the imaging sintering point instrument through the main interface; preferably, the heating speed is set to 10°C / min, and the image shooting frequency is 1 image for every 10°C temperature rise; when heating the basalt fiber, mineral wool fiber, zirconium-containing aluminum silicate fiber corresponding to the carbon fiber test block, the heating temperature range is set to 20-1200°C, and the image shooting temperature range is set to 400-1200°C; when heating the carbon fiber corresponding to the carbon fiber test block, the heating temperature range is set to 20-700°C, and the image shooting temperature range is set to 400-700°C;
[0143] 2.2.3. Rotate the camera of the imaging sintering point instrument so that the binder test block to be heated is in the center of the camera display screen, and adjust the focal length of the camera until the carbon fiber test block to be heated can be clearly seen on the camera display screen;
[0144] 2.2.4. Place a camera protector between the camera head and the heating furnace, and make the camera lens, camera protector and the carbon fiber test block to be heated in the same straight line;
[0145] 2.2.5. Turn on the power of the heating furnace;
[0146] 2.2.6. Heat the carbon fiber test block by operating the software, and take images of the adhesive test block within the image taking temperature range based on the image taking frequency to obtain images at different temperature points;
[0147] 2.2.7. When the heating temperature reaches 700℃ or 1200℃, save the image and end the heating;
[0148] 2.2.8. After the carbon fiber test block cools to room temperature, take it out of the heating furnace and turn off the heating furnace, operating software and host power in turn.
[0149] 2.3 Image Processing
[0150] 2.31. Open ImageJ image analysis software;
[0151] 2.3.2. Extract images at different temperature points;
[0152] 2.3.3. Select the polygonal selection tool to connect the borders of the image at any temperature point;
[0153] 2.3.4. Calculate the pixels of the image at any temperature point through the analysis menu of the main interface of ImageJ image analysis software;
[0154] 2.3.5. Repeat 2.3.3-2.3.4 to calculate the pixels of the image at different temperature points.
[0155] Through the above operations, pixels of images of the carbon fiber test blocks of basalt fiber / mineral wool fiber / carbon fiber / zirconium-containing aluminum silicate fiber at different temperature points are obtained.
[0156] 2.4 Pixel Processing
[0157] With temperature as the abscissa and pixels as the ordinate, a temperature-pixel diagram of basalt fiber / mineral wool fiber / carbon fiber / zirconium-containing aluminum silicate fiber is drawn.
[0158] 2.5 Analysis
[0159] 2.5.1. Volume change of basalt fiber at high temperature
[0160] like Fig.11 As shown in Figure 2, at 400°C, the basalt fiber specimen has a certain shape; Fig.12 As shown in the figure, the basalt fiber specimen has completely melted into liquid at 1200℃, which means that basalt fiber can hardly withstand 1200℃ and cannot be used as the refractory material of fire retardant coating.
[0161] like Fig.13 As shown in the figure, as the temperature increases, the crystal form of basalt fiber changes. When the temperature exceeds 1130℃, the volume shrinks significantly, but the degree of shrinkage cannot be directly seen from the image.
[0162] like Fig.14 As shown in the figure, between 400℃-1200℃, as the temperature rises, the pixels are shrinking, that is, the volume of basalt fiber is gradually shrinking, but the shrinkage is not obvious. When the temperature rises to around 1150℃, the volume of basalt fiber shrinks sharply. This is because when the temperature reaches about 1150℃, the basalt fiber has melted. Although some high-temperature resistant black silicate binder supports its volume, the volume of basalt fiber is much larger than that of black silicate binder, so even part of the black silicate binder is dissolved in the basalt fiber melt, so from a macroscopic point of view, the volume of basalt fiber shrinks sharply.
[0163] It can be seen from the temperature-pixel graph that basalt fiber is not suitable for the fire-resistant layer material of steel structure fire-resistant coating. This is because when the fire temperature rise curve reaches 4.0h, according to the standard temperature rise curve, the average temperature of the fire scene is 1153℃. The temperature is near the melting temperature of basalt fiber, but at this time, the temperature of some fire scenes has exceeded 1200℃, so basalt fiber is not suitable for use as the fire-resistant layer of fire-resistant coating.
[0164] 2.5.2 Volume change of mineral wool fibers at high temperatures
[0165] like Fig.15 As shown in Figure 2, at 400°C, the mineral wool fiber specimen has a certain shape; Fig.16 As shown, there is no obvious change in the shape of the mineral wool fiber specimen at 1200°C, which indicates that the mineral wool fiber can withstand a high temperature of 1200°C and can be used as a fire-resistant layer material for fire-retardant coatings.
[0166] like Fig.17 As shown in the figure, the images of mineral wool fibers at different temperatures show that the size of the mineral wool fiber image does not change significantly as the temperature rises. When the temperature exceeds 1200°C, the volume shrinkage is not obvious, but the degree of volume change cannot be directly seen from the image.
[0167] like Fig.18 As shown in the figure, it can be seen from the temperature-pixel that between 400℃-950℃, the pixel of the image decreases, that is, the volume of the mineral wool fiber is gradually reduced. When the temperature reaches about 950℃, the volume of the mineral wool fiber is reduced to the maximum. This is because during the heating process of the mineral wool fiber, part of the mineral material is melted from a certain shape of solidification to liquid, and the volume shrinks. Although the volume of the mineral wool fiber increases with the increase of temperature, the volume of the mineral wool fiber is not enough to offset the volume of the mineral wool shrinkage. Therefore, the volume of the mineral wool fiber decreases macroscopically. When the temperature of the mineral wool fiber exceeds about 950℃, the volume of the mineral wool increases. This is because the quartz crystal form in the mineral wool fiber changes: α quartz in the mineral wool fiber is transformed into phosphotquartz, and the volume expansion rate of quartz increases sharply, resulting in an increase in the volume of the mineral wool fiber. However, the increased volume does not exceed the volume at 400℃, so from the overall trend, the volume of the mineral wool fiber is decreasing during the entire heating process. When the temperature approaches 1200℃, the volume of the mineral wool fiber decreases again, indicating that the mineral wool fiber is melted again. Therefore, when mineral wool fibers are used as refractory materials, there are certain risks when they are subjected to a temperature of 1153°C.
[0168] 2.5.3 Volume change of carbon fiber at high temperature
[0169] like Fig.19As shown, at 400°C, the carbon fiber test block has a regular shape, and at 700°C the volume of the carbon fiber test block shrinks sharply, which shows that carbon fiber cannot withstand the high temperature of 700°C and cannot be used as the fire-resistant layer material of fire-retardant coatings.
[0170] like Fig. 20 As shown in the figure, the image of carbon fiber at different temperatures shows that as the temperature rises, the size of the carbon fiber image shrinks. When the temperature exceeds 590°C, the volume shrinks significantly, but the degree of volume change cannot be directly seen from the image.
[0171] like Fig.21 As shown in the figure, it can be seen from the temperature-pixel change that between 400℃-550℃, the pixels become smaller, that is, the volume change of carbon fiber is small, which shows that in this temperature range, carbon fiber is relatively stable. When the temperature exceeds about 550℃, the pixels shrink linearly and sharply, which shows that when the temperature reaches 550℃, carbon fiber cannot be used as a reinforcing material for fire retardant coatings. This is because when the temperature exceeds 550℃, the carbon fiber is oxidized by oxygen in the air to generate carbon dioxide gas, which leaves the fire retardant coating. The remaining volume is black silicate binder.
[0172] 2.5.4 Volume change of zirconium-containing aluminum silicate fibers at high temperatures
[0173] like Fig. 22 As shown in Figure 2, at 400°C, the zirconium-containing aluminum silicate fiber specimen has a regular shape; Fig.23 As shown in the figure, the volume of the zirconium-aluminum silicate fiber specimens shrank sharply at 1200°C, which shows that the zirconium-aluminum silicate fibers can withstand high temperatures of 1200°C and can be used as fire-resistant layer materials for fire-retardant coatings. Comparing the image shapes of the zirconium-aluminum silicate fibers at 400°C and 1200°C, the image features of the two are almost the same, which shows that the volume of the zirconium-aluminum silicate fibers is relatively stable at high temperatures.
[0174] like Fig.24 As shown, the images of zirconium-containing aluminum silicate fibers at different temperatures. As the temperature increases, the image size of the zirconium-containing aluminum silicate fibers does not change significantly.
[0175] like Fig.25 As shown, it can be seen from the temperature-pixel change that in the range of 400℃-1200℃, the volume of zirconium-containing aluminum silicate fibers is relatively stable, which is beneficial to maintaining the volume stability of the fire-retardant coating and is suitable for use as a fire-resistant reinforcement material for the fire-retardant coating.
[0176] 2.6. Based on the volume change law of basalt fiber / mineral wool fiber / carbon fiber / zirconium-containing aluminum silicate fiber at high temperature, the best reinforcement material for fire retardant coatings can be quickly screened out.
[0177] By taking images of each fiber at different temperatures, using image analysis software to calculate the pixels at different temperatures, and then drawing a temperature-pixel graph, the volume change pattern of the fiber under high temperature conditions can be clearly seen from the graph.
[0178] As the temperature rises, the volume of basalt fiber gradually decreases, but the reduction is not obvious. When the temperature rises to around 1150℃, the volume of basalt fiber decreases sharply. There are some risks when basalt is used as a refractory material. However, it can be used as a thermal insulation material for multi-layer fire retardant coatings.
[0179] During the heating process, as the temperature rises, the volume of the mineral wool fiber expands from decreasing to increasing. When the temperature of the mineral wool fiber exceeds about 950℃, the volume of the mineral wool increases. The characteristics of mineral wool can be used in combination with the temperature-increasing volume of black silicate to prepare a fireproof and heat-insulating layer with a relatively stable volume.
[0180] Between 400℃ and 550℃, the volume change of carbon fiber is small, which means that in this temperature range, carbon fiber is relatively stable. When the temperature exceeds about 550℃, the carbon fiber pixel linearity shrinks sharply. This means that when the temperature reaches 550℃, carbon fiber cannot be used as a reinforcing material for fire retardant coatings.
[0181] During the entire heating process, the volume of zirconium-containing aluminum silicate fiber is relatively stable at high temperature and can be used as a reinforcing material for fire retardant coatings.
[0182] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solutions of the present invention, rather than limiting them, and certainly not limiting the patent scope of the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In other words, any changes or modifications made to the main design concept and spirit of the present invention that have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention in other related technical fields is also included in the patent protection scope of the present invention.
Claims
1. A method for rapid screening of fireproof materials, characterized in that: The following steps are involved: By taking images of various fireproof materials at different temperatures, using image analysis software to calculate the pixels at different temperatures, and then drawing a temperature-pixel graph, the appropriate fireproof materials can be quickly screened out based on the volume change pattern of each fireproof material under high temperature conditions shown on the graph.
2. A method for rapid screening of fireproof materials according to claim 1, characterized in that: The fireproof material comprises an adhesive bond and / or reinforcing fibers.
3. A method for rapid screening of fireproof materials according to claim 1 or 2, characterized in that: The steps of taking images of various fireproof materials at different temperatures are as follows: placing the fireproof material sample in the center of the heating furnace tray of the imaging sintering point tester, setting the heating temperature range to 20-1200°C, the heating speed to 5-20°C / min, the image shooting frequency to take one image for every 5-20°C rise in temperature, and the image shooting temperature range to 400-1200°C. When the heating temperature reaches the set maximum value, the test data is saved and the heating program is ended.
4. A method for rapid screening of fireproof materials according to claim 1, characterized in that: Calculating pixels at different temperatures includes the following steps: S1. Open ImageJ software. S2. Extracting images of each temperature point; S3. Select a polygonal border selection tool to connect the borders of the sample image; S4. Calculate the pixels of the image through the analysis menu of the main interface; S5. Repeat steps S2-S4 to count the image pixels at different temperatures respectively.
5. A method for rapid screening of fireproof materials according to claim 1 or 2, characterized in that: The step of drawing the temperature-pixel graph includes: drawing the temperature-pixel graph of the inorganic binder according to the temperature and pixel table of the image processing, with the temperature as the horizontal coordinate and the volume as the vertical coordinate.
6. A method for rapid screening of fireproof materials according to any one of claims 1 to 5, characterized in that: When the fireproof material is a binder, the steps include: S11, selecting two adhesives, a white silicate adhesive and a black silicate adhesive, and preparing adhesive test blocks respectively; S12, using an imaging sintering point instrument, taking images of each adhesive test block at different temperatures; S13, using ImageJ image analysis software to calculate the pixels of the image; S14, plotting a temperature-pixel graph for each adhesive with temperature as the abscissa and pixels as the ordinate; S15. Based on the images of each adhesive test block at different temperatures and the temperature-pixel map of each adhesive, the volume change law of each adhesive at high temperature is obtained. Preferably, in S11, the steps of making the adhesive test block are as follows: S111. Take a beaker, add 90-110 g of white silicate binder / black silicate binder into the beaker, add 15-20 g of distilled water into the beaker with a plastic dropper, and then stir rapidly with a glass rod for 1-3 minutes to obtain a uniform thick paste A; S112, transfer paste A into the small holes of the plastic porous plate, the diameter of the small holes is 10 mm, and the height is 10 mm; use a plastering knife to smooth the paste along the upper and lower surfaces of the plastic porous plate, and then use a glass rod with a diameter of 8 mm to poke out the paste A, and place it flat on white paper, and dry it naturally at room temperature for 24 hours to obtain a dry adhesive test block; Preferably, the specific operation of S12 is as follows: S121, pulling out the heating furnace tray of the image sintering apparatus, placing the dried binder test block in the center of the heating furnace tray, and then pushing the heating furnace tray into the heating furnace of the image sintering apparatus; S122, turn on the host of the imaging sintering point instrument, start the operating software, and set the heating speed, heating temperature range, image shooting frequency and image shooting temperature range of the imaging sintering point instrument through the main interface; preferably, the heating speed is set to 10°C / min, the heating temperature range is set to 20-1200°C, the image shooting frequency is to shoot one image every time the temperature rises by 10°C, and the image shooting temperature range is set to 400-1200°C; S123, rotating the camera head of the imaging sintering point instrument so that the binder test block to be heated is in the center of the camera display screen, and adjusting the focal length of the camera until the binder test block to be heated can be clearly seen on the camera display screen; S124, placing a camera protector between the camera head and the heating furnace, and making the camera lens, the camera protector and the adhesive test block to be heated in the same straight line; S125, turning on the power of the heating furnace; S126, heating the adhesive test block by operating the software, and capturing images of the adhesive test block within the image capturing temperature range based on the image capturing frequency to obtain images at different temperature points; S127, when the heating temperature reaches 1200°C, save the image and end the heating; S128, after the adhesive test block cools to room temperature, it is taken out of the heating furnace, and the heating furnace, operating software and host power are turned off in sequence; Preferably, the specific operation of S13 is as follows: S131, open ImageJ image analysis software; S132, extracting images at different temperature points; S133, select a polygonal border selection tool to connect the border of the image at any temperature point; S134, calculating the pixels of the image at any temperature point through the analysis menu of the main interface of the ImageJ image analysis software; S135. Repeat S133-S134 to calculate the pixels of the image at different temperature points.
7. A method for rapid screening of fireproof materials according to any one of claims 1 to 5, characterized in that: When the fireproof material is reinforced fiber, the method comprises the following steps: S21, select four types of fibers, namely basalt fiber, mineral wool fiber, carbon fiber and zirconium-containing aluminum silicate fiber as reinforcing materials; S22, respectively preparing carbon fiber test blocks of each fiber; S23, using an imaging sintering point instrument to take images of each carbon fiber test block at different temperatures; S24, using ImageJ image analysis software to calculate the pixels of the image; S25, using temperature as the abscissa and pixel as the ordinate, drawing a temperature-pixel graph of each carbon fiber; S26. Based on the images of each carbon fiber test block at different temperatures and the temperature-pixel map of each carbon fiber, obtain the volume change law of each carbon fiber at high temperature; Preferably, the specific operation of S22 is as follows: S221, cut any fiber into short shreds with a length of 2 mm, take 2 g, add about 0.2 g of black silicate binder and an appropriate amount of water to make a paste B; S222. Transfer paste B into the small holes of a plastic porous plate with a diameter of 10 mm and a height of 10 mm. Gently compact paste B and smooth paste B along the upper and lower surfaces of the plastic porous plate with a plastering knife. Use a glass rod with a diameter of 8 mm to poke out paste B and place it flat on white paper. Dry it naturally at room temperature for 48 hours to obtain a dry carbon fiber test block.
8. A method for rapid screening of fireproof materials according to claim 6, characterized in that: The specific operation of S23 is as follows: S231, pulling out the heating furnace tray of the image sintering instrument, placing the dried carbon fiber test block in the center of the heating furnace tray, and then pushing the heating furnace tray into the heating furnace of the image sintering instrument; S232, turn on the host of the imaging sintering point instrument, start the operating software, and set the heating speed, heating temperature range, image shooting frequency and image shooting temperature range of the imaging sintering point instrument through the main interface; preferably, the heating speed is set to 10°C / min, and the image shooting frequency is 1 image per 10°C temperature rise; when heating the basalt fiber, mineral wool fiber, zirconium-containing aluminum silicate fiber corresponding to the carbon fiber test block, the heating temperature range is set to 20-1200°C, and the image shooting temperature range is set to 400-1200°C; when heating the carbon fiber corresponding to the carbon fiber test block, the heating temperature range is set to 20-700°C, and the image shooting temperature range is set to 400-700°C; S233, rotating the camera head of the imaging sintering point instrument so that the binder test block to be heated is in the center of the camera display screen, and adjusting the focal length of the camera until the carbon fiber test block to be heated can be clearly seen on the camera display screen; S234, placing a camera protector between the camera head and the heating furnace, and making the camera lens, the camera protector and the carbon fiber test block to be heated in the same straight line; S235, turning on the power of the heating furnace; S236, heating the carbon fiber test block by operating the software, and capturing images of the binder test block within the image capturing temperature range based on the image capturing frequency to obtain images at different temperature points; S237, when the heating temperature reaches 700° C. or 1200° C., save the image and end the heating; S238. After the carbon fiber test block cools to room temperature, take it out of the heating furnace, and turn off the heating furnace, operating software and host power in turn.
9. A method for rapid screening of fireproof materials according to claim 6, characterized in that: The specific operation of S24 is as follows: S241, open ImageJ image analysis software; S242, extracting images at different temperature points; S243, select a polygonal border selection tool to connect the border of the image at any temperature point; S244, calculating the pixels of the image at any temperature point through the analysis menu of the main interface of the ImageJ image analysis software; S245, repeat S243-S244 to calculate the pixels of the image at different temperature points.
Citation Information
Patent Citations
Fireproof coating applicable to 800-1200 DEG C, and preparation method and application thereof
CN119019872A
